Analysis on pure e-commerce congestion effect, productivity effect and profitability in China. (March 2017) - Yang, Zhuofan; Shi, Yong; Yan, Hong
Abstract: This paper examines the relationship of e-commerce congestion effect, productivity effect and profit generation in China. The technique of Data Envelopment Analysis (DEA) is used to measure returns to scale and total factor productivity in e-commerce. The results show that e-commerce firms achieve productivity growth but suffer from input congestion. Congestion weakens profitability and leads to negative returns of inputs to outputs. This finding offers a new insight to explain the determinants of profit change. This research enriches production theory of internet companies, and helps managers strengthen their profitability by measuring the existence of congestion and eliminating input congestion resources. Highlights: E-commerce firms achieved productivity growth but suffered from input congestion. Industry-level congestion has a negative effect on e-commerce profitability. Productivity effect has positive correlation with e-commerce profitability. Our work fills the gap of empirical research on e-commerce congestion measurement. This research offers a new explanation as to the determinants of profit change.